2021
DOI: 10.5194/wes-6-1473-2021
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effects in the long-term correction of short-term wind measurements using reanalysis data

Abstract: Abstract. Measure–correlate–predict (MCP) approaches are often used to correct wind measurements to the long-term wind conditions on-site. This paper investigates systematic errors in MCP-based long-term corrections which occur if the measurement on-site covers only a few months (seasonal biases). In this context, two common linear MCP methods are tested and compared with regard to accuracy in mean, variance, and turbine energy production – namely, variance ratio (VR) and linear regression with residuals (LR).… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…year of temporal coverage. Taylor et al (2004as reported via Carta et al, 2013, Weekes and Tomlin (2014), and Basse et al (2021) reported that wind speed errors were within 4%, 4.8%, and 4%, respectively, using three months of onsite measurements. The performance of long-term predictions using less than one year of on-site measurements varied according to the season(s) during which the onsite measurements were taken.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…year of temporal coverage. Taylor et al (2004as reported via Carta et al, 2013, Weekes and Tomlin (2014), and Basse et al (2021) reported that wind speed errors were within 4%, 4.8%, and 4%, respectively, using three months of onsite measurements. The performance of long-term predictions using less than one year of on-site measurements varied according to the season(s) during which the onsite measurements were taken.…”
Section: Introductionmentioning
confidence: 95%
“…For their experiment in the United Kingdom, Weekes and Tomlin (2014) found that the smallest errors occurred when using measurements taken in early spring or fall. Basse et al (2021) performed MCP tests in Germany using linear regression and variance ratio algorithms and found that using variance ratio produced overestimates when using summer measurements and underestimations when using winter measurements, with the opposite trend noted for linear regression.…”
Section: Introductionmentioning
confidence: 99%